Modulatory Efficiency of Vitamin C (Ascorbic Acid) on Collagen-Induced Platelet Aggregation and Dysfunction - Onwuka, Osah Martins; Adigwe, Chukwukadibie; Adheke, Oghenefego Michael; Elem, Chamberlin Jamike; Hart, Josiah Soipiriala (Biology, Medicine, & Natural Product Chemistry, 2024)
Platelet aggregation, coagulation, and activation are crucial for hemostasis. Collagen treatment can impair hemostatic processes leading to bleeding disorders like thrombosis; vitamin C may mitigate these effects.  Hence, modulatory efficiency of vitamin C on collagen-induced platelet aggregation and dysfunction was investigated. Thirty (30) Wistar rats (135g-155g) were divided equally into; Group 1 (Control), Group 2 (Collagen-induced), and Group 3 (Collagen + Vitamin C treated). Platelet aggregation, prothrombin time, bleeding time, fibrinogen levels assessed coagulation and platelet function. Thromboxane B2 and P-selectin levels measured platelet and endothelial activation. Platelet count, mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit (PCT) evaluated platelet production and size variability. Statistical significance was set at p < 0.05. Group 2 exhibited higher platelet aggregation, prolonged prothrombin and bleeding times and elevated fibrinogen, thromboxane B2, and P-selectin levels, along with increased platelet count, MPV, PDW, and PCT, compared to Group 1. Group 3 showed significant reductions in all these parameters compared to Group 2 (p < 0.05). Vitamin C demonstrated significant modulatory effect on collagen-induced platelet aggregation and dysfunction which suggests that vitamin C may have therapeutic potential in mitigating platelet dysfunction and coagulation impairments associated with collagen-induced pathophysiological conditions.